A review of user-centred design methods for designing a portable oil spill skimmer - Abdullah, Lokman; Ramanathan, Rprakash; Syed Mohamed, Muhammad Syafiq; Md Fauadi, Muhammad Hafidz Fazli (Technoscience Publications, 2022)
Boom and skimmer are mechanical techniques in Oil Spill Response and Recovery (OSRR) that collect oil from the water surface. However, there are several drawbacks of using boom and skimmer, such as the oil could pass over the boom during strong wind and high tides. Moreover, the currently available oil skimmer designed by the engineers is heavy-duty; in consequence, it is ineffective in shallow water. Thus, there is a need to develop a portable oil spill skimmer to complement the current drawbacks. Several journals on the fabrication of the oil spill skimmer were reviewed. Findings from literature shows that the development of oil spill skimmer lacks user requirements when designing a portable oil spill skimmer. This article provides a systematic review of Kansei Engineering and the Analytical Hierarchy Process in the product development process. Therefore, Kansei Engineering and Analytical Hierarchy Process (AHP) can be incorporated in the early stage of designing a portable oil spill skimmer. This paper also includes the application of Kansei Engineering and AHP in design research articles. Findings from observed articles indicate a lack of design and development technologies relating to products for environmental protection; the AHP and Kansei Engineering application is somewhat lacking. Moreover, the fabrication of an oil spill skimmer focuses more on technical specifications and includes fewer user requirements. As a result, the characteristics such as ease of use, robustness, and safety cannot be evaluated. The AHP and Kansei Engineering methodology can be extended to the design and manufacture of products for environmental protection.